Perbandingan Algoritma CART dan C.4 5 Pada Citra Tandan Buah Sawit Untuk Mengetahui Tingkat Kematangan Dalam Penentuan Harga - Agustin, Riris; Sarjon Defit; Sumijan (Universitas Putra Indonesia YPTK Padang, 2024)
Information technology is a means and infrastructure of a system method to organize, send, interpret, use, process, obtain, and store data in a meaningful and useful way. Oil palm is a tropical plant originating from West Africa. The advantage of this plant is that it can also be planted outside its place of origin, including Indonesia. This plant has been widely cultivated in the form of plantations and factories in various regions in Indonesia. Oil palm is an industrial plant that is used as a raw material for vegetable oil, industrial oil, and fuel. Oil palm is important for Indonesia because it creates jobs for local people and is a source of foreign currency for the country. Oil palm plants begin to flower and form fruit after 2-3 years. The fruit will ripen about 5-6 months after pollination. The ripening process of oil palm fruit can be seen from the change in color of the fruit's skin. The fruit will turn orange-red when ripe. When the fruit is ripe, the oil content in the fruit flesh is at its maximum. If it is too ripe, the oil palm fruit will fall from the stalk of the bunch. This study aims to assess the maturity of a bunch of oil palm fruit. The methods used in this study are CART and C.4 5. Each method has several stages that will produce entropy and gain values ​​that will later form a decision tree. The dataset consists of 37 data consisting of 10 criteria originating from Ramp 789 Batang Peranap. Based on the implementation of the C4.5 algorithm and the CART algorithm in determining the level of ripeness of oil palm fruit bunches on RAMP 789 Batang Peranap which produces an accuracy of 98.00%. These results are obtained based on Process data with testing using the RapidMiner application, which produces a Decision tree that is useful as a reference for decisions in determining whether or not oil palm fruit bunches are ripe, which so far have only been predicted.